The Influence of Scrabble Toys on the Initial Reading Ability of Children Aged 5-6 Years at Al-Furqan Minasa Islamic Kindergarten UPA Makassar: PERMAINAN SCRABBLE TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK - Raning, Widya Ayu Rosita (JAPRA (Jurnal Pendidikan Raudhatul Athfal), 2024)
This study aims to find out whether there is an influence of scrabble toys on the beginning reading ability of children aged 5-6 years at Al-Furqan Islamic Kindergarten Minasa Upa. The research approach used is a quantitative approach with the type of Quasi Experiment Design research with a Non Equivalent Control Group Design research design. The population in this study amounted to 54 students of group B at Al-Furqan Minasa Islamic Kindergarten Upa Makassar. The sampling in this study is purposive sampling. The sample in this study was 20 children with 10 children as the experimental group and 10 children as the control group. The data collection techniques used are observation, tests, and documentation. The data analysis techniques used are descriptive statistics and non-parametric analysis, namely (Wilcoxon signad rank test). The results of the study showed changes in children's creativity seen from the average before and after treatment. From the results of the research that has been carried out, it can be seen that there is an effect of the use of scrabble games on the ability to read at beginning reading skills in children aged 5-6 years at Al-Furqan Minasa Islamic Kindergarten Upa Makassar.